Optical Solitons and Stability Analysis in Ring-Cavity Fiber System with Carbon Nanotube as Saturable Absorber - Aliyu, Aliyu Isa; İnç, Mustafa; Yusuf, Abdullahi; Baleanu, Dumitru (Iop Publishing Ltd, 2018)
This paper addresses the ring-cavity fiber laser system. A class of gray and black soliton solutions of the model are reported by adopting an appropriate envelope ansatz. Further more, the modulation instability (MI) of the equation is studied using the linear-stability analysis (LSA) technique and the MI gain spectrum is derived. Some physical interpretations and analysis of the results obtained are also presented.
Keywords: complex envelope ansatz solution; ring-cavity fiber laser system; linear stability analysis; optical solitons